Examining the mediating effects of perceived risk and benefits on trust and continuance intention - Putri Nofzil, Fellina; Firman, Firman (Universitas Negeri Padang, 2024)
The aim of this research is to analyze (1) the influence of trust on the continuance intention of Tokopedia users in Padang City. (2) the influence of trust on the perceived risk of Tokopedia users in Padang City. (3) the influence of trust on the perceived benefits of Tokopedia users in Padang City. (4) the influence of perceived risk on the continuance intention of Tokopedia users in Padang City. (5) the influence of perceived benefit on the continuance intention of Tokopedia users in Padang City. (6) the influence of trust on the continuance intention of Tokopedia users in Padang City with perceived risk as a mediating variable. (7) the influence of trust on the continuance intention of Tokopedia users in Padang City with perceived benefit as a mediating variable. This type of research is quantitative descriptive research, the number of samples in this research is 180 respondents using purposive sampling techniques, the data analysis method uses SEM analysis using the Smart PLS 4 application. The research results are 1) there is a significant influence between trust and the continuance intention of Tokopedia users in Padang City. (2) there is a significant influence between trust on the perceived risk of Tokopedia users in Padang City. (3) there is a significant influence between trust on the perceived benefits of Tokopedia users in Padang City. (4) there is a significant influence between perceived risk on the continuance intention of Tokopedia users in Padang City. (5) there is a significant influence between perceived benefit on the continuance intention of Tokopedia users in Padang City. (6) there is a significant influence between trust on the continuance intention of Tokopedia users in Padang City with perceived risk as a mediating variable. (7) there is a significant influence between trust on the continuance intention of Tokopedia users in Padang City with perceived benefit as a mediating variable.